1991
DOI: 10.7863/jum.1991.10.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early third-trimester ultrasound screening for intrauterine growth retardation.

Abstract: Ultrasound fetal biometry is widely used for detection of intrauterine growth retardation (IUGR). Since fetal growth is a dynamic process, studies estimating validity of ultrasound near term may not be applicable earlier in pregnancy. This study applied receiver operating characteristic (ROC) curve analysis to ultrasound biometric data obtained at 26‐34 weeks gestation to predict fetuses destined to be IUGR at birth. In this method, the area under the curve (theta) is the index of performance. Sixty‐nine (9%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 11 publications
3
31
0
Order By: Relevance
“…However, the rarest and severest form of the disease is fortunately the one that is easier to diagnose either by its common association with maternal hypertension or by second trimester abnormal fetal growth and/or uterine Doppler studies. Recent research has shown that early severe growth restriction may be detected from the first trimester using combinations of fetal biometry, maternal biochemistry and uterine Dopplers . The prediction models presented in our study apply for the late SGA.…”
Section: Discussionmentioning
confidence: 89%
“…However, the rarest and severest form of the disease is fortunately the one that is easier to diagnose either by its common association with maternal hypertension or by second trimester abnormal fetal growth and/or uterine Doppler studies. Recent research has shown that early severe growth restriction may be detected from the first trimester using combinations of fetal biometry, maternal biochemistry and uterine Dopplers . The prediction models presented in our study apply for the late SGA.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, some research findings support the use of a small (<10th percentile) abdominal circumference as a sensitive predictor of small for gestational age [7-10]. However, small abdominal circumference alone, in the absence of growth restriction has not been associated with adverse neonatal outcomes [1-5,7,8,11-17]. …”
Section: Introductionmentioning
confidence: 99%
“…However, most SGA babies remain unnoticed until birth, even when routine third-trimester ultrasound is performed [3,4]. Moreover, according to pregnancy audits, most instances of avoidable stillbirth are related with a failure to antenatally detect SGA [5].…”
Section: Introductionmentioning
confidence: 99%